COVID-19 and developmental origins of health and disease. (April 2021) - Forestieri, Stefano; Pintus, Roberta; Marcialis, Maria Antonietta; Pintus, Maria Cristina; Fanos, Vassilios
Abstract: From the moment of the identification of SARS-CoV-2 as an etiological agent of the severe clinical pictures of pneumonia that were being slowly observed all over the world, numerous studies have been conducted to increase the knowledge about what was an unknown virus until then. The efforts were mainly aimed to acquire epidemiological, microbiological, pathogenetic, clinical, diagnostic, therapeutic and preventive information in order to increase the available weapons to fight an infection which was rapidly taking on the characteristics of the pandemic. Given the topicality of the problem, not everything has yet been fully understood and clarified, especially in the maternal-fetal‑neonatal field, where we are beginning to question what could be the outcomes of newborn babies born to mothers who contracted SARS-CoV-2 infection during pregnancy. Thus, the aim of this review is to analyze the long-term outcomes of this infection that could affect the offspring, regardless of a possible maternal-fetal transmission, focusing on, above all, the role of maternal immune activation and the expression of the Angiotensin-converting enzyme 2 (ACE2) in particular at the placental level. Highlights: The debate on the possibility of a vertical transmission of SARS-CoV-2 is still open. Fetuses of COVID-19 mothers can develop many diseases in life, regardless of a SARS-CoV-2 maternal-fetal transmission. MIA can interfere with the fetal brain development, leading to an increased risk of developing neuropsychiatric disorders. The alteration of ACE2-Ang (1–7) -MasR axis by maternal SARS-CoV-2 infection causes IUGR, SGA, heart and metabolic diseases. There is the need for long-term follow-up of infants born to COVID-19 positive mothers.